Prevalence, Co-Occurrence, and Correlates of Substance and Behavioral Addictions Among American Indian Adolescents in California. (March 2021) - Sussman, Steve; Unger, Jennifer B.; Begay, Cynthia; Moerner, Lou; Soto, Claradina
The present study investigated the prevalence and co-occurrence of addictions to tobacco, alcohol, other drugs, food/eating, the internet, texting, video games, shopping, love, sex, exercise, work, and gambling among American Indian (AI) youth in California. As with previous work in other cultural groups, the most prevalent addictions were love, internet, and exercise, though prevalence and co-occurrence of these addictions were relatively high among AI youth. A negative life events measure was associated with all the addictions, suggesting that life stressors are associated with high rates of multiple types of addictions among AI youth. There is a need for more research to better understand the relations of life stressors with multiple addictions among AI youth as well as how to remediate these behaviors.